Implementación de un plan de seguridad y salud en el trabajo para reducir los peligros y riesgos en el área de servicios públicos de la Municipalidad Provincial de Chepén - Chavarria Burgos, Víctor Gianfranco (2020)
The Provincial Municipality of Chepén, does not have a health and safety plan at work that allows it to safeguard the integrity of its employees from any danger that may cause damage to health, especially in the most critical area, the Public Utilities Department; therefore, it has been proposed to implement a safety and health plan in the workplace for said dependence, in order to minimize the hazards and control the existing risks, thus avoiding occupational accidents or diseases, as well as sanctions imposed by the Ministry of Labor, according to law. The present work began with a baseline study of health and safety at work of the Provincial Municipality of Chepén and the sub management of public services, then the hazard identification, risk assessment and control matrix were applied. with the purpose of identifying the main hazards and risks to which the collaborators of the public services area are exposed, and from this propose controls according to the provisions of the Occupational Safety and Health Act, its regulation and its modification. Then we proceeded to analyze the statistics of occurrence of accidents and lost days occurred in the Public Services Area of the Provincial Municipality of Chepén during the periods 2016-2018, with this we were able to obtain the safety indicators. Finally, with all the information obtained, the Occupational Health and Safety Plan was developed and the economic evaluation was established, where the feasibility of the project to implement the Safety and Health Plan at Work in the Provincial Municipality of Chepén was determined determining the decrease in costs due to work accidents.